A business plan and strategy for Big Sky Shires & Equine Services - Hoagland, Leanne K. (Kansas State University, 2007)
This thesis is the vehicle that I have used to outline a thorough small business plan for our personal business Big Sky Shires & Equine Services. While working toward my MAB Degree, I realized there were a lot of things that I could implement from the program into our business that would help us succeed in the equine industry. I was able to research the industry that we were in to gain a better understanding of how to market and plan for the future. In the back of my mind I started to ask a lot of questions and soon found that we needed a business plan that would answer many questions about the future of our business. The first part of the thesis is the history of the equine industry with a look at US history, outlook for the future and strategic issues affecting the industry. The second part of the thesis is a history of Big Sky Shires & Equine Services. This history tells where the business has come. The third portion, of the thesis is the small business plan that is the most thorough we could put together. A lot of thought and time went into the document that we plan to implement and update quarterly as needed. The final portion of the thesis is our conclusion followed by a detailed appendix of the corresponding documents for operating our business.
Keywords: Equine; Business Plan; Equine Business; Agriculture, General (0473); Economics, Agricultural (0503); Education, Agricultural (0517)